Feasibility of a family‐centered intervention for depressed older men in primary care. (25th August 2019) - Hinton, Ladson; La Frano, Erika; Harvey, Danielle; Alfaro, Eduardo Delgadillo; Kravitz, Richard; Smith, Andrew; Apesoa‐Varano, Ester Carolina; Jafri, Asma; Unutzer, Jurgen
Abstract : Objective: Families provide considerable support to many older adults with depression, yet few intervention studies have sought to include them. Family participation in depression treatment aligns with the preferences of older men, a group at high risk for depression under treatment. This study examined the feasibility of a family‐centered depression intervention for older men in a primary care setting. Methods: A clinical trial was conducted in a Federally Qualified Health Center (FQHC) in California's Central Valley. Depressed older men (age 50 and older) were allocated to usual care enhanced by depression psychoeducation or a family‐centered depression intervention delivered by a licensed clinical social worker. Intervention feasibility was assessed in terms of recruitment, retention, and extent of family engagement. The PHQ‐9 was administered at baseline, 1, 3, and 6 months. Results: For more than 6 months, 45 men were referred to the study; 31 met the inclusion criteria, 23 were successfully enrolled, and 20 (88%) participated in more than or equal to one treatment sessions. Overall, 85% (11 of 13) of men allocated to the intervention engaged a family member in more than or equal to one session and 54% (7 of 13) engaged the family member in more than or equal to three sessions. While men in both groups showed evidence of a significant decline in PHQ‐9 scores early on, which attenuated over time, there were no significant between group differences. Conclusions: Our family‐centered depression intervention showed acceptable feasibility on the basis of a variety of parameters. Future research on family‐based approaches may benefit from longer duration and more intensive treatment as well as additional strategies to overcome recruitment barriers.